“The Effect of Training and Development on Employee Performance in a Private Tertiary Institution in Ghana” (Case Study: Pentecost University College (Puc) - Ghana) - Ampomah, Philipina (Asian Journal of Social Sciences and Management Studies, 2016)
Training and development is one of the key factors in improving employee performance in most organisations today. Evidence derived from research showed that there is now a broad discussions amongst commentators that skills training and career development improve employee performance in the organization. The study focused on the effect of training and development on employee performance in a private tertiary institution in Ghana; a case study of Pentecost University College. The study used the simple random sampling technique to select staff from all levels of management. A high response rate of ninety-six percent was obtained using the personal method of data collection, based on which the analysis was made using the frequency tables and charts. The study found out that employees are aware of the purpose of training in the organisation, the training objectives are clear to them before the training as well as the selection criteria. The study also found out that employees are motivated through training; and training and development results into higher performance. The study recommended that training and development of all staff should be vigorously pursued and made compulsory.